The New Science of Astrobiology From Genesis of the Living Cell to Evolution of Intelligent Behaviour in the Universe - Chela-Flores, Julian (Cellular Origin, Life in Extreme Habitats and Astrobiology, 2001)
Astrobiology is a very broad interdisciplinary field covering the origin, evolution, distribution, and destiny of life in the universe, as well as the design and implementation of missions for solar system exploration. A review covering its complete spectrum has been missing at a level accessible even to the non-specialist. The last section of the book consists of a supplement, including a glossary, notes, and tables, which represent highly condensed 'windows' into research ranging from basic sciences to earth and life sciences, as well as the humanities. These additions should make The New Science of Astrobiology accessible to a wide readership: scientists, humanists, and the general reader will have an opportunity to participate in one of the most rewarding activities of contemporary culture